Diagnosis and Surgical Management of a Paratesticular Cyst in a Rehabilitating Juvenile Male Green Turtle (Chelonia mydas) - Weisbrod, Tatiana C.; Stacy, Nicole I.; Stedman, Nancy L.; Norton, Terry M. (Frontiers in Veterinary Science, 2020)
A juvenile green turtle (Chelonia mydas) undergoing rehabilitation for cold-stunning exhibited asymmetric bulging of the left caudal plastron and was diagnosed with a large intra-coelomic mass based on radiographical findings. Ultrasonography further identified a fluid-filled structure within the caudal coelom. Cytological evaluation of fluid obtained from the structure was consistent with a transudate and thus a cyst of unknown origin was suspected. Computed tomography imaging was pursued to further characterize the extent and location of the mass which occupied approximately 50% of the total coelomic cavity volume. Conservative management with monitoring and occasional drainage of the mass did not result in improvements; thus, an exploratory laparoscopy for further investigation and surgical planning was elected. Intra-coelomic surgery was performed to remove a thick-walled cystic mass associated with the left gonad. Histopathology confirmed a paratesticular cyst continuous with, and possibly originating from, the epididymis. Post-surgical recurrence of the cyst was not appreciated and the animal was successfully released 1 year after admission. Unrelated to the cyst, the turtle developed acute severe anemia on two occasions throughout rehabilitation that responded to modification of antimicrobial treatment and subsequent steroid administration. To the authors’ knowledge, this is the first report of a paratesticular cyst in a reptile.